Kejadian Kematian pada Pasien Infeksi COVID-19 Tahun 2021: Studi Kasus di Kabupaten Blora - Al Isynaini, Izha Fajar; Cahyati, Widya Hary (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: The number of confirmed cases of COVID-19 in Blora Regency is 13.565 the number of death reaching 1.041 cases. Five public health centers as research location were included in the 10 health centers with the highest death cases in Blora Regency. The purpose of this study was to determine the risk factors associated with the incidence of death in patients with COVID-19 infection. Methods: This type of research is analytic observational with a case-control design. The sample was set at 68 cases and 68 controls with purposive sampling technique. The instrument used is a recording sheet. Data were analyzed using chi-square test and logistic regression test. Results: Result showed that age (OR=5,187; 95% CI=2,428-11,084), hypertension (OR=2,962; 95% CI=1,366-6,420), diabetes mellitus (OR=4,487; 95% CI=2,080-9,682), cardiovascular disease (OR=11,552; 95% CI=1,435-92,972), and chronic kidney disease (OR=8,933; 95% CI=1,080-73,525) are associated with the incidence of death in COVID-19 patients. Conclusion: Age, hypertension, diabetes mellitus, cardiovascular disease and chronic kidney disease are associated with the incidence of death in COVID-19 patients. The probability of COVID-19 patients aged ≥ 50 years, having hypertension, diabetes mellitus, cardiovascular disease and chronic kidney disease to die is 99%.